Clima y Cultura Organizacional en el Centro de Matriculación Vehicular del Municipio de Loja - Castillo León, Elton Jhon (2023)
The organizational climate and culture are crucial aspects that directly influence the performance and results of the work team in the Vehicle Registration Center of the City Hall of Loja, as well as the satisfaction and motivation of the employees. The aid of the study was to establish the relationship between the work climate and organizational culture in order to propose an improvement plan that contributes to optimize the institution's performance. The research was designed as non-experimental, correlational, with a mixed, qualitative and quantitative approach. The selected sample consisted of 30 employees of the Vehicle Technical Review Center of the Loja canton. For data collection, a survey was applied to the employees of the center and statistical tests were used for data processing. In addition, an exhaustive literature review was carried out on organizational climate and culture to collect valuable information on the perceptions and experiences of employees in their job within the center. The main results showed that employees reported good communication between bosses and employees, felt secure in their work, received support from their colleagues, felt responsible for their work, considered that their work was recognized and valued by their superiors. There was a good work environment, established acts were known, conflicts were resolved appropriately and identified with their jobs. Therefore, it can be affirmed that the results showed a positive perception by employees regarding the work climate and organizational culture of the Vehicle Technical Review Center of the City Hall of Loja. Keywords : Structure, responsibility, reward, risk, warmth